Quality improvement interventions and the transformation of organizational practices: A review of health sector and general management literature - Saulpic, Olivier; Zarlowski, Philippe; Bérard, Emilie; Denis, Jean-Louis (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2025)
While research on “materiality” has enhanced our understanding of how material artefacts affect organizations, questions remain about how these artefacts achieve practical efficacy. This concern has been explored in healthcare literature, especially with regards to quality improvement (QI) interventions. However, there is still no consensus on the conditions under which QI interventions lead to improved quality of care. Through a critical interpretative synthesis of the literature on QI interventions from both healthcare and management fields, we identify four research approaches. We show that none of these approaches considers together the materiality of QI interventions, their efficacy, and the overall interaction with context and actors. This leads us to propose avenues for future research on the practical efficacy of material artefacts.